Analisis pelaksanaan program pemberian keringanan dan pembebasan denda Pajak Kendaraan Bermotor dan Bea Balik Nama Kendaraan Bermotor berdasarkan Pergub Sulut No 61 Tahun 2020 (Studi pada Kantor Samsat Pembantu Sitaro) - Medellu, Bellatryx Yulsrivita; Kalangi, Lintje; Suwetja, I Gede (Yayasan Widyantara Nawasena Raharja, 2024)
Motor Vehicle Tax (PKB) and Motor Vehicle Name Transfer Fee (BBNKB) are local taxes governed by the local tax incentive regulation outlined in Sulawesi Utara Governor Regulation No. 61 of 2020. This research aims to determine whether the implementation of the PKB and BBNKB relief and waiver program at the Sitaro Samsat Assistant Office is in accordance with Governor Regulation No. 61 of 2020; understand the recognition, measurement, presentation, and disclosure of the motor vehicle tax relief and waiver program at the Sitaro Samsat Assistant Office; and identify the causes of the decline in PKB and BBNKB revenue in 2023. The method used is descriptive qualitative research. Based on the findings from the Sitaro Samsat Assistant Office, it can be concluded that: the implementation of the tax relief and waiver program for motor vehicle taxes and name transfer fees has complied with Governor Regulation No. 61 of 2020; Revenue recognition is based on the values stated in the relevant documents at the time of payment. Measurement is conducted based on the fair value received, and the presentation and disclosure of motor vehicle tax revenues must be separated and reported according to the type of income as incentives (PKB and BBNKB) and penalty waivers, with all revenues presented in Indonesian Rupiah in accordance with applicable accounting standards. Revenue disclosure in operational reports includes clear classifications: types of revenue received such as PKB, BBNKB, penalty waivers, implementation periods, and revenue amounts; The causes of the decline in motor vehicle tax and name transfer fee revenues include incentive policies, timing of implementation, socialization, and taxpayer awareness.